Cross Countries Economic Performances - SPF Approach - Alali, W Y (University of Oxford, 2022)
Created in 2009-2010; The differences in technical inefficiency (inefficient allocation of production inputs) explain the diverse cross-country economic performances, using estimating a “global” stochastic production frontier (SPF) model, and (Rodrik (2000)’s taxonomy of institutions), to compare the mean level of technical inefficiency for each country per period. Our model, consider three variables dimensions – human capital, openness, and institutions. Institutions are more fundamental to the sources of technical inefficiency. Specifically, the rule of law has a direct impact on improving technical efficiency. Democracy and sound money, do not have a direct impact on technical efficiency. However, their interactions with human capital are statistically significant. It points out the possibility that a minimum level of human capital matters for these two aspects of institutions to have any impact on technical efficiency. Regulation, on the other hand, shows a threshold effect. That said, after reaching a threshold level of regulation, excessive regulation leads to technical inefficiency